2018
DOI: 10.1097/jom.0000000000001274
|View full text |Cite
|
Sign up to set email alerts
|

A Follow-Up Study on Return to Work in the Year After Reporting an Occupational Injury Stratified by Outcome of the Workers’ Compensation System

Abstract: Objective:The aim of this study was to compare return rates to work between different groups according to the decision from the workers’ compensation.Method:Register data on disability benefits were used to describe return rates to work in Kaplan–Meier curves and association with decision on compensation claims. Disability benefits were granted by the municipalities independently of any compensation claim if sick-listed.Results:Claimants with ongoing claims were the group with the largest proportion remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…This can limit labor market participation, reduce annual income, and therefore threaten household livelihoods [ 35 , 36 , 37 ]. It has long been criticized that those who are compensated due to industrial accidents through the compensation system show more unfavorable outcomes than those uncompensated [ 38 ]. This study was conducted to identify the changes in income before and after the industrial accidents of affected workers whose recovery periods had ended.…”
Section: Discussionmentioning
confidence: 99%
“…This can limit labor market participation, reduce annual income, and therefore threaten household livelihoods [ 35 , 36 , 37 ]. It has long been criticized that those who are compensated due to industrial accidents through the compensation system show more unfavorable outcomes than those uncompensated [ 38 ]. This study was conducted to identify the changes in income before and after the industrial accidents of affected workers whose recovery periods had ended.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, a return-to-work is easier for workers who are male, younger, and have better health, a low level of disability from injury, a shorter recovery period, better hospital quality and a greater interest in returning to work from the physician [2,17,18,19,20,21,22,23]. Some additional studies evaluated compensation for industrial accidents or the return-to-work and changes in income after industrial accidents [3,10,24,25,26]. However, those studies were based on either the degree of disability after the accident or the status of workers before the accident.…”
Section: Introductionmentioning
confidence: 99%
“…Not participating in work or education is associated with both economic consequences and psychological distress. Several studies have been published on return to work after trauma; however, the overall public health perspective tended to be restricted owing to small sample sizes, or focus on selected groups of patients with specific injuries or specific mechanisms of injury. Two large population‐based studies from the Victorian State Trauma Registry in Australia reported long‐term follow‐up data regarding return to work, but included only the most severely injured patients.…”
Section: Introductionmentioning
confidence: 99%